⎩ ⎨ ⎧ m 2 + n ⋮ n 2 − m m + n 2 ⋮ m 2 − n
How many pairs of positive integers ( m , n ) satisfy the conditions above?
Notation: If a ⋮ b , then a is divisible by b , or b divides a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The problem states "For example, a ⋮ b means that a is divisible by b , or a divides b . " The part where it says a divides b is incorrect.
Also, I think (1,2) and (2,1) should be included as solutions.
If the problem stated that m and n are distinct positive integers, then the number of solutions is 4 . But since it wasn't stated that way, if the variables can have the same value, it would be 6 .
Log in to reply
Thanks. I've updated the answer to
6
. Those who previously answered
6
has been marked correct.
In the future, if you have concerns about a problem's wording/clarity/etc., you can report the problem. See how here .
1 2 3 4 5 6 7 |
|
1 2 3 4 5 6 |
|
Problem Loading...
Note Loading...
Set Loading...
⎩ ⎨ ⎧ m 2 + n ⋮ n 2 − m m + n 2 ⋮ m 2 − n ( 1 )
⇔ { m 2 + n ≥ n 2 − m m + n 2 ≥ m 2 − n
⇔ { ( m − n + 1 ) ( m + n ) ≥ 0 ( n − m + 1 ) ( m + n ) ≥ 0
⇔ { m − n + 1 ≥ 0 n − m + 1 ≥ 0 (Because m , n are positive integers, m + n > 0 )
⇔ − 1 ≤ m − n ≤ 1
As m , n are positive integers, m − n ∈ { − 1 , 0 , 1 }
Case 1: m − n = − 1 ⇔ m = n − 1
n 2 + m ⋮ m 2 − n ⇒ m 2 − n n 2 + m ∈ Z
⇔ ( n − 1 ) 2 − n n 2 + n − 1 ∈ Z
⇔ n 2 − 3 n + 1 n 2 + n − 1 ∈ Z
⇔ n 2 − 3 n + 1 ( n 2 − 3 n + 1 ) + 4 n − 2 ∈ Z ⇒ n 2 − 3 n + 1 4 n − 2 ∈ Z
⇒ 4 n − 2 ≥ n 2 − 3 n + 1 ⇔ n 2 − 7 n + 3 ≤ 0
⇒ 2 7 − 3 7 ≤ n ≤ 2 7 + 3 7
As n is a positive integer, n ∈ { 1 , 2 , 3 , 4 , 5 , 6 }
Because m = n − 1 , we have ( m , n ) = ( 1 , 2 ) , ( 2 , 3 ) , ( 3 , 4 ) , ( 4 , 5 ) , ( 5 , 6 )
Substitute these results into ( 1 ) , the solutions satisfying ( 1 ) are ( m , n ) = ( 1 , 2 ) , ( 2 , 3 )
Case 2: m − n = 0 ⇔ m = n
m 2 − n n 2 + m ∈ Z
⇔ n 2 − n n 2 + n ∈ Z
⇔ n 2 − n ( n 2 − n ) + 2 n ∈ Z ⇒ n ( n − 1 ) 2 n ∈ Z ⇔ n − 1 2 ∈ Z
⇒ n − 1 ≤ 2 ⇒ n ≤ 3
As n is a positive integer, n ∈ { 1 , 2 , 3 }
Because m = n , we have ( m , n ) = ( 1 , 1 ) , ( 2 , 2 ) , ( 3 , 3 )
Substitute these results into ( 1 ) , the solutions satisfying ( 1 ) are ( m , n ) = ( 2 , 2 ) , ( 3 , 3 )
Case 3: m − n = 1 ⇔ m = n + 1
m 2 + n ⋮ n 2 − m ⇒ n 2 − m m 2 + n ∈ Z
⇔ n 2 − n − 1 ( n + 1 ) 2 + n ∈ Z
⇔ n 2 − n − 1 n 2 + 3 n + 1 ∈ Z
⇔ n 2 − n − 1 ( n 2 − n − 1 ) + 4 n + 2 ∈ Z ⇒ n 2 − n − 1 4 n + 2 ∈ Z
⇒ 4 n + 2 ≥ n 2 − n − 1 ⇔ n 2 − 5 n − 3 ≤ 0
⇒ 2 5 − 3 7 ≤ n ≤ 2 5 + 3 7
As n is a positive integer, n ∈ { 1 , 2 , 3 , 4 , 5 }
Because m = n + 1 , we have ( m , n ) = ( 2 , 1 ) , ( 3 , 2 ) , ( 4 , 3 ) , ( 5 , 4 ) , ( 6 , 5 )
Substitute these results into ( 1 ) , the solutions satisfying ( 1 ) are ( m , n ) = ( 2 , 1 ) , ( 3 , 2 )
Conclusion: There are 6 solutions satisfying ( 1 ) , which are ( m , n ) = ( 1 , 2 ) , ( 2 , 1 ) , ( 2 , 2 ) , ( 2 , 3 ) , ( 3 , 2 ) , ( 3 , 3 )